Physical Meaning of Hidden Rays in Wedge Diffraction - Kim Se-Yun (PROCEEDINGS OF THE 2019 INTERNATIONAL CONFERENCE ON ELECTROMAGNETICS IN ADVANCED APPLICATIONS (ICEAA), 2019)
The physical meaning of hidden rays is illustrated clearly on the shadow boundary of a perfectly conducting wedge. In previous, the supplementary plane was adopted to help the visualization of the hidden rays on shadow boundary. A new illustration of the hidden ray-tracing is presented here by introducing the extended complementary air region satisfying the edge condition. Hence it may easily found that hidden rays on shadow boundary are governed by the same tracing rule of ordinary rays on lit boundary.
Keywords: diffraction; null; wedge; null; physical optics; null; ray-tracing; null; edge condition